Reflexos do processamento de cana-de-açúcar bisada na qualidade do açúcar VHP - Costa, Gustavo Henrique Gravatim [UNESP]; Masson, Igor dos Santos [UNESP]; Roviero, Juliana Pelegrini [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (My University, 2014)
The aim of this study was to compare the quality of clarified juice and VHP (Very High Purity) sugar produced from “bisada” sugarcane and an early maturation variety, at the beginning of harvest. The experiment was conducted at Usina São Martinho S/A, Pradópolis,SP (Brazil). The process of juice clarification and sugar production was conducted at the Laboratory of Technology of Sugar and Alcohol in the College of Agricultural and Veterinary Sciences at the Universidade Estadual Paulista (FCAV/UNESP), Jaboticabal (SP). The experimental design was randomized, and two varieties were used: SP83-2847 (“bisada” sugarcane) and RB855156 (early maturation), with twelve replications for technological analysis and four replications for sugar production. The clarification process and the clarified juice was evaluated in terms of settling rates, volume of sludge that formed, total soluble solids, pH, turbidity, total phenolic compounds, starch and color. The sugar was characterized regarding the percentage of apparent sugar, color, total phenolic compounds, starch, filterability, humidity and safety factor. It was verified that the processing of the juice clarification was not affected by the processing of the “bisada” sugarcane. However, the clarified juice from the SP83-2847 variety had a more intense color and a higher total soluble solids value. The sugar produced from the “bisada” sugarcane presented similar quality to the early maturation variety. It was concluded that the processing of “bisada” sugarcane at the start of the harvest did not affect the juice clarification and resulted in VHP sugar of a quality similar to that of the early maturation variety.
Reflections of the processing of “Bisada” sugarcane in the quality of VHP sugar
Keywords: Saccharum spp; Simple defecation; Sugar; Sugarcane; VHP